Morphometric analysis of some metric characters of two Macrobiotus species (Eutardigrada, Macrobiotidae) - Oscar LISI; Maria Grazia BINDA; Erminia CONTI; Giovanni PILATO; Giovanni COSTA (Journal of Limnology, 2007)
A study on individual variability was carried out on some metric characters of two species of Eutardigrada Macrobiotidae: Macrobiotus diffusus and Macrobiotus areolatus. Other than range of variability for various characters considered, correlation analysis and regression analysis for some of them were carried out by means of binary comparisons. By means of prediction ellipses, which were always determined with a probability of P = 99.9%, it was possible to hypothesize - with an error risk of 0.1% - if an individual whose data were outside the confidence interval belonged to a species. The value of the pt index relative to the point of insertion of the stylet supports is particularly significant, showing variations with extremely limited and independent dispersion both for body length and for buccal tube length.